Geophysics Canada - An Informative Update - McNeely, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary The annual CSEG convention, which was held this year at the Calgary Inn Calgary, Alberta, April 17th to 19th, 1974 has evolved over the last few years to the point where it has been regarded as the foremost meeting of geophysical exploration expertise in Canada. This annual conference was designed to be technical in format and its prime purpose has been to promote the exchange and dissemination of technical data through all branches of the geophysical profession in Canada. While the 1974 convention was ostensibly oriented toward technical content, the dominant overtones implicit in many of the papers were in fact political. This was of course predictable because of the uncertain future presently facing the resource industries (and consequently the geophysical industry) in Canada as a result of recent federal policy statements. The 1974 convention attracted 750 registrants, a decrease of roughly eight per cent from the previous year. Papers at the conference were grouped under four general subdivisions: 1. data acquisition, 2. data processing, 3. interpretation, 4. general topics, with a considerable overlap between these classifications.